FAKTOR RISIKO HIPERTENSI PADA REMAJA - Fira Mardianti; Dewi Rachmawati; Suprajitno Suprajitno (Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang, 2022)
Introduction: hypertension can occur in adults and adolescents, many factors influence the occurrence of hypertension in adolescents. The purpose of this study was to determine the risk factors that can affect the occurrence of hypertension in adolescents. Methods: The research design is a traditional review, with literature sources from the google scholar database, with inclusion criteria for articles published in 2016-2020, which can be downloaded in their entirety, equipped with DOI or ISSN or E-ISSN and cross-sectional and case-control research designs. A search using the keyword risk factor